Substolides A–G, germacrane sesquiterpenoids from Salvia substolonifera. (December 2015) - Fang, Lianglian; Lin, Weiwei; Qiu, Guanguan; Cai, Yuan; Yan, Pengcheng; Cai, Xiaoqing; Li, Wencan; Tu, Hongfeng; Dong, Jianyong
Graphical abstract: Ten germacrane sesquiterpenoids, including three previously known, were isolated from the whole plants of Salvia substolonifera E.Peter. Four 8-acetylation derivatives were obtained by chemical transformation. Several of the compounds significantly inhibited VEGF-induced human umbilical vein endothelial cell proliferation in vitro . Highlights: Ten germacrane sesquiterpenoids including 3 previously known were isolated. Four 8-acetylation derivatives were obtained by chemical transformation. Structures were elucidated by intensive spectroscopic methods and X-ray crystallography. Several compounds showed significant in vitro inhibition of VEGF-induced HUVECs proliferation. Abstract: Chemical investigation of the whole plants of Salvia substolonifera E.Peter yielded seven germacrane sesquiterpenoids, substolides A–G (1 –7 ), an ethoxylated artifact (8 ), and two known analogues, 6 β -tigloyloxyglechomafuran (9 ) and castanin F (10 ). Four germacrane 8-acetylation derivatives (1a –4a ) were obtained by chemical transformation. Their structures and relative or absolute configurations were elucidated by intensive spectroscopic methods, and single-crystal X-ray diffraction analysis. Compounds1a –4a, and5 –10 were evaluated for their in vitro anti-angiogenic effects. Compounds7 and9 significantly inhibited VEGF-induced human umbilical vein endothelial cell (HUVEC) proliferation in vitro, with IC50 values of 16.15 ± 0.19, and 4.03 ± 0.26 μM, respectively. The structure activity relationship of these compounds is discussed.